Current status of cassava processing technology in semiarid areas of Central and West Africa. In The small processor and development of local food industries for market economy - Tshiunza, M.; Okechukwu, R.U.; Bokanga, M.; Dixon, Alfred G.O. (2004)
A village level survey was organised in 200 villages in semiarid areas of Burkina Faso, Chad, Ghana, Niger, and Nigeria using structured questionnaires in order to provide baseline information on the status of cassava processing technology as part of the collaborative study on cassava in semiarid areas (COSCASA). The results of the study indicate a very low level of cassava processing knowledge in the area. "Boiled roots" is the most common and unique form of comsuming cassava in most villages of the region. The study also found that in most villages people eat cassava products not locally processed; these included mostly garri, cassava flour and to a lesser extent attieke. These products were brought from neighoring villages or countries. Lack of processing knowledge, insufficient supply of raw material (cassava roots), and lack of equipment are the most important reasons given by farmers for not processing the above "imported cassava products" in their villages. Most farmers indicated that they wished to learn gari processing technology.